2016
DOI: 10.1111/acem.13100
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Utilization in Children <36 Months Is Not an Independent Risk Factor for Maltreatment

Abstract: In efforts to identify children at risk for maltreatment, objective assessments such as PED utilization are potential markers to utilize to aid in recognition. Unfortunately, there are many risk factors for increased PED utilization that act as confounders for this marker. Future work is necessary to identify children at risk for maltreatment in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…We also did a manual search to identify additional papers using the references list of these 15 studies, which did not result in any additional studies matching our review criteria (Figure 1). 32‐46 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also did a manual search to identify additional papers using the references list of these 15 studies, which did not result in any additional studies matching our review criteria (Figure 1). 32‐46 …”
Section: Resultsmentioning
confidence: 99%
“…The interrater reliability was strong among the two researchers who were involved in the quality assessment (Cohen's kappa = 0.83). We were unable to make a definite assessment for some of the tool's quality measures, but the overall quality of the studies was high 33,34,36‐40,42,44,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant research in this field has been carried out by Guenther and co-workers (2009), who reported that abused childrencompared to controlswere more likely to have made prior emergency department visits. In a subsequent study, the importance of confounding variables was highlighted, and the authors noted that frequent emergency department visits was not an independent risk factor for maltreatment in small children (MacNeill, Cabey, Kluge, Norton, & Mitchell, 2016).…”
Section: Study Vmentioning
confidence: 99%
“…On a related note, Guenther and coworkers reported that children subjected to abuse, compared to controls, more often had made prior emergency department visits. A subsequent study that highlighted the importance of confounding variables found that frequent emergency department visits were not an independent risk factor for maltreatment in children younger than 36 months of age .…”
mentioning
confidence: 99%